2021
DOI: 10.1007/s10773-021-04967-x
|View full text |Cite
|
Sign up to set email alerts
|

Tighter Monogamy and Polygamy Relations of Quantum Entanglement in Multi-qubit Systems

Abstract: We investigate the monogamy relations related to the concurrence, the entanglement of formation, convex-roof extended negativity, Tsallis-q entanglement and Rényi-α entanglement, the polygamy relations related to the entanglement of formation, Tsallis-q entanglement and Rényi-α entanglement. Monogamy and polygamy inequalities are obtained for arbitrary multipartite qubit systems, which are proved to be tighter than the existing ones. Detailed examples are presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 44 publications
1
15
2
Order By: Relevance
“…Then, by making full use of the new inequality, we establish a general framework of monogamy relations for arbitrary quantum states. The lower bounds obtained by us are tighter than existing ones [30][31][32][33][34][35][36][37][39][40][41][42]. To illustrate our results obviously, two examples are presented in term of the µ-th power of concurrence.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Then, by making full use of the new inequality, we establish a general framework of monogamy relations for arbitrary quantum states. The lower bounds obtained by us are tighter than existing ones [30][31][32][33][34][35][36][37][39][40][41][42]. To illustrate our results obviously, two examples are presented in term of the µ-th power of concurrence.…”
Section: Introductionmentioning
confidence: 60%
“…The red line represents the lower bound from the result in [39] with k = 2. The yellow line represents the lower bound from the result in [40] with k = 2. The purple line represents the lower bound from the result in [34][35][36][37] with k = 2.…”
Section: Discussionmentioning
confidence: 99%
“…This polygamy relation has been generalized to multipartite systems for various assisted entanglement measures such as the squared concurrence of assistance C 2 a [28], entanglement of assistance E a [17,29], the βth (0 ≤ β ≤ 2) power of convex-roof extended negativity of assistance N β a [30]. Similar to the monogamy relation, the corresponding tighter polygamy relations have also been established for different kinds of assisted entanglements [22,25,26].…”
mentioning
confidence: 96%
“…According to the CKW inequality, the monogamy relation was generalized to other entanglement measure such as convex-roof extended negativity N [18][19][20]. Moreover, it has been shown that these entanglement measures to the αth power do satisfies tighter monogamy relations of tripartite systems and multipartite systems [23][24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation